KECERDASAN INTERPERSONAL SISWA: Analisis Upaya Guru dalam Mengembangkannya di SMP 03 Rejang Lebong - Warsah, Idi; Aprilian, Mela; Rahmaningsih, Sri (Tarbawiyah Jurnal Ilmiah Pendidikan, 2020)
The teacher is the spearhead in developing children's intelligence at school, including social or interpersonal intelligence. Such an assumption motivates the researchers to conduct a study at SMPN 03 Rejang Lebong by applying a qualitative approach. This study draw the following conclusion: first, PAI teachers’ efforts to develop students’ interpersonal intelligence were carried out by managing classroom properly, always giving motivation, using methods which can support the development of students' interpersonal intelligence such as discussions, peer-tutoring, demonstrations, group assignments, and questions and answers. In the meantime, the media used were laptops, posters and textbooks. The inhibiting factors in the process of developing students' interpersonal intelligence were low students’ interest, family environment, and learning hours, while the supporting factors in the process of developing students' interpersonal intelligence were teachers’ motivation, facilities and infrastructure, methods used by teachers in the learning processes, extracurricular, and colleagues.